Investigation on dielectric relaxation Of PMMA-grafted natural rubber incorporated with LiCF3SO3 - Yap, K.S.; Teo, L.P.; Sim, L.N.; Majid, Siti Rohana; Arof, Abdul Kariem (Elsevier, 2012)
Natural rubber (NR) grafted with 30 wt% poly(methyl methacrylate) (PMMA) and designated as MG30 has been added with varying amounts of LiCF3SO3. X-ray diffraction (XRD) shows the samples to be amorphous. Fourier transform infrared (FTIR) spectroscopy indicates complexation between the cation of the salt and the oxygen atom of the C-O and -COO- groups of MG30. From electrochemical impedance spectroscopy (EIS), MG30 with 30 wt% LiCF3SO3 salt exhibits the highest ambient conductivity of 1.69 x 10(-6) S cm(-1) and lowest activation energy of 0.24 eV. The dielectric behavior has been analysed using dielectric permittivity (epsilon'), dissipation factor (tan delta) and dielectric modulus (M*) of the samples. The dielectric constant of pure MG30 has been estimated to be similar to 1.86. (C) 2012 Elsevier B.V. All rights reserved.